2019
DOI: 10.21608/ajnsa.2018.3107.1071
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Ameliorative Effect of Bee Venom Against Damage and Inflammation Induced in Gamma-Irradiated Rats

Abstract: The aim of the present study is investigating the possible protective effect of Bee Venom (BV) against gamma radiation induced damage and inflammation in male rats. Gamma-irradiation (6 Gy) resulted in a significant elevation in the level of tumor necrosis factor-alpha (TNF-α) , interleukin-6 (IL-6) , creatinine kinase-MB (CK-MB) and cardiac troponin I (cTnI), lactate dehydrogenase (LDH), creatine phosphokinase (CPK), serum aspartate transaminase (AST) and alanine transaminase (ALT) , serum glucose, malondiald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
3
5
0
Order By: Relevance
“…While groups treated with bee venom using both doses (0.5 and 1.23 mg/kg) and the combined therapy (metformin and atorvastatin) showed a significant decline in malondialdehyde levels in comparison to the positive control. These results follow a previous study, 79 which reported that the treatment with bee venom leads to a reduction in the malondialdehyde levels in heart tissue compared to positive control because of the anti-oxidative activity of bee venom.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…While groups treated with bee venom using both doses (0.5 and 1.23 mg/kg) and the combined therapy (metformin and atorvastatin) showed a significant decline in malondialdehyde levels in comparison to the positive control. These results follow a previous study, 79 which reported that the treatment with bee venom leads to a reduction in the malondialdehyde levels in heart tissue compared to positive control because of the anti-oxidative activity of bee venom.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, they are compatible with other studies, 77,78 which found that the activities of CK-MB and LDH were raised in STZ-diabetic rats, likely due to disruption of myocardial structure induced by reactive oxygen species, while groups treated with bee venom using both doses (0.5 and 1.23 mg/kg) and the combined therapy (metformin and atorvastatin) showed a significant reduction ( P < 0.0001) in CK-MB and LDH activities when compared to the positive control. These results are in accordance with Shaaban and Hamza, 79 who stated that treatment with bee venom resulted in a reduction in CK-MB and LDH activities compared to the positive control. The ameliorating effect of bee venom on CK-MB and LDH activities could be because of its antioxidant effect by suppressing the formation of free radicals, scavenging free radicals, preventing lipid peroxidation of membranes, and maintaining membrane integrity, thus limiting the outflow of these enzymes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a similar study, they found decreased SOD, CAT and GSH activity according to the control group in rat liver irradiated with 6 Gy gamma-ray. In the bee venom + irradiated group, biochemical parameters, there were significant changes compared to the irradiated group (29).…”
Section: Discussionmentioning
confidence: 81%
“…Bee venom protects from the gamma and X-ray radiation in numerous assessment systems ( Gajski and Garaj-Vrhovac 2009 ). Also, BV has antioxidant efficacy and can neutralize free radicals and protect the body from toxic radiation ( Shaaban and Hamza 2019 ). BV defends the bone marrow cells from chromosomal abnormalities (aberrations) in vivo in the Wistar mice model ( Varanda and Tavares, 1998 , Bellik, 2015 ).…”
Section: Pharmacological Properties Of Honey Bee Venommentioning
confidence: 99%